Komodifikasi Citra Perempuan Muslim dalam Dunia Fashion: Analisis Semiotika Tayangan Dua Hijab Trans 7 - Mega Kusuma Wardani (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2018)
This study discusses how the image of Muslim women who are commodified in television shows, namely Dua Hijab program on Trans 7. Dua Hijab are a show that provides information about fashion hijab references for Muslim women. This research is motivated by the media not only as a medium of communication and information, but also as a medium for ideological battles and also used as a power to regulate society. The community will tend to ignore the true meaning, the substantial meaning, and finally get caught up in the commodity fethism that makes people become consumptive. The problem in this study is how TRANS 7 forms commodification in the content of Dua Hijab television shows and How TRANS 7 shapes the image of women in the content of Dua Hijab television shows. In this study, researchers analyzed the Country Style episode of Dua Hijab shows using Roland Barthes' semiotics analysis. The results of this study indicate that Dua Hijab provides some fashion hijab references for Muslim women. Dua Hijab gives reference to fashion hijab in various fashion themes that are adapted to wearing the hijab and the smell of Islam. In this case, Dua Hijab portrayes Muslim women as being fashion sensitive and appearing stylish and fashionable. This is what Vincent Moscow has described as a commodification of content. Commodification prioritizes visible physical form, rather than substantially meaning. This causes the community to only be trapped in the apparent meaning of existence. The community will tend to ignore the true meaning, the substantial meaning, and finally get caught up in the commodity fethism that makes the society become consumptive